Health-disease Process of Acute Chagas Disease According to One Health Approach - , Victor Viana da Graça; , Juarez Antônio Simões Quaresma (Archives of Current Research International, 2024)
One Health approach emerges as an innovative perspective to understand the health-disease process of acute Chagas disease (ACD). This study aimed to identify scientific evidence on the health-disease process of ACD through one health approach. This integrative literature review study had as guiding question: what is the current scientific evidence on the health-disease process of ACD according to One Health approach? A greater number of studies can be seen from 2021. The following categories were defined from the 13 studies found: One Health approach to Chagas disease; Spatial epidemiology of Chagas disease; Control and transmission factors of Chagas disease; Health indicators in Chagas disease; and Educational technology in Chagas disease. The results of this literature review, while showing greater proportions of studies involving ACD control and transmission, also demonstrate fields of study that are still little explored by national and international scientific literature, such as in the field of technologies for ACD, reflecting a large gap to be filled with future research on ACD. This study contributed to expanding the debate on the importance of an integrative approach in health research and encouraging the search for more comprehensive solutions for ACD.